Propofol, morfina e metadona como moduladores da dor em lambaris submetidos a estímulo nociceptivo - Rorig, Maria Cecilia de LIma (2022)
In the decades, as recent investigations into different and nociceptive processes have intensified through research into non-scientific research, research to investigate the existence of different processes. The lambari (Astyanax lacustris) has been used as an experimental model in different areas of research and currently, chemical stimuli are the most used for the study of nociception in fish. Among the observed opioids, it is known that opioids are more indicated for the treatment of moderate pain to several acute events and during the acute duration. Furthermore, the possibility of a noxious stimulus for fundamental responses is one of the criteria used for the animals' ability to perceive. Thus, the present tested three behavioral changes of propofol (2mg/Liter; 5 mg/Liter and 10 mg/Liter) and the logical change in lambaris (Astyanax lacustris) studies to identify behavioral and acetic differences in the mouth related to pain. It also evaluated the effects of morphine and methadone at different doses (5, 10, 25, 50 and 100 mg/kg) in fish with and without stimulation. As a concentration of 5 mg/liter of relevant results properties such as fast safety, lower occurrence of hyperactivity and action in the animals tested. Acetic acid injection showed physical and behavioral changes such as increased breathing, lack of eating behavior, hyperactivity at the injection site, among others. The tested doses of morphine (10 and 25 mg/Kg) and methadone (10 and 25 mg/Kg) are shown to be safe and capable of modulating physiological and behavioral changes to pain in fish. However, more research is found to investigate protocols, since there are different behavioral and physiological responses in researches that evaluate pain control in animals.